Clinical Grade Regulatory CD4+ T Cells (Tregs): Moving Toward Cellular-Based Immunomodulatory Therapies - Duggleby, Richard; Danby, Robert David; Madrigal, J. Alejandro; Saudemont, Aurore (Frontiers in Immunology, 2018)
Regulatory T cells (Tregs) are CD4+ T cells that are key players of immune tolerance. They are powerful suppressor cells, able to impact the function of numerous immune cells, including key effectors of inflammation such as effector T cells. For this reason, Tregs are an ideal candidate for the development of cell therapy approaches to modulate immune responses. Regulatory T cell (Treg) therapy has shown promising results so far, providing key knowledge on the conditions in which these cells can provide protection and demonstrating that they could be an alternative to current pharmacological immunosuppressive therapies. However, a more comprehensive understanding of their characteristics, isolation, activation, and expansion is needed to be able design cost effective therapies. Here we review the practicalities of making Tregs a viable cell therapy, in particular, discussing the challenges faced in isolating and manufacturing Tregs and defining what are the most appropriate applications for this new therapy.